Student Management in Improving Arabic Communication Competence and its Implications for Students Self Determination - Siti Rumania; Asep Maulana; Bambang Irawan; Yusuf Olawale Owa-Onire Uthman (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This article aims to describe the management of students carried out by teachers at the As-Sunniah Kencong Islamic Boarding School for all students to master Arabic materials to help improve their ability to communicate in Arabic and the implications for student self-determination learning. The research approach used is qualitative research. Data collection techniques utilize observation, interviews, and documentation studies. In this study, researchers used several stages of data analysis, namely the reduction stage, the data presentation stage, making temporary conclusions, and verification activities. The study results concluded that two hours of lessons are scheduled weekly with material according to the level. Meanwhile, the management of students outside the classroom includes Daily Arabic Conversation, Arabic Speech Practice, and Arabic Speech Contests. The management of students in learning Arabic at the As-Sunniah Kencong Islamic Boarding School is that the learning systems and methods are pretty good and effective, learning is in line with Arabic learning theories, the awareness and interest of the students to speak Arabic have grown, and language environment has been built.